THE INFLUENCE OF STRATEGIC HRM ON ORGANIZATIONAL COMPETITIVENESS (International Journal of Food and Nutritional Sciences, 2022)
Strategic Human Resource Management (SHRM) plays a pivotal role in enhancing organizational competitiveness by aligning human capital with long-term business objectives. Unlike traditional HRM, which focuses primarily on administrative tasks, SHRM integrates human resources into the core strategy of the organization, recognizing employees as key drivers of performance, innovation, and overall success. This paper explores the influence of SHRM on organizational competitiveness, emphasizing its impact on talent management, leadership development, workforce performance, and organizational culture. One of the primary ways SHRM enhances competitiveness is through effective talent management. By attracting, developing, and retaining top talent, HR ensures that the organization has the right people in place to achieve strategic goals. Furthermore, SHRM focuses on leadership development, ensuring that future leaders are equipped to drive change and innovation, which are essential for staying competitive in a rapidly changing business environment.